An Analysis of the Impact of Hindi Language on the Language Use of Young Pakistani Females - Amna Fajar (University of Chitral Journal of Linguistics and Literature, 2020)
This study investigates the Hindi language impact on Pakistani young females’language. The young generation of a country is considered as a strong pillar fornational development. The purpose of this study is to analyze the major effects ofwatching Indian dramas on the language of Pakistan's young females. For this study,the researcher has selected two colleges and used the qualitative method that involvesclose-ended questions. In the sampling process, the non-probability samplingtechnique has been used which includes judgmental sampling. For the study, 70samples from the target population have been collected. The study records students’normal T.V watching hours, their preference for using the Hindi language words intheir daily routine, and the place of their acknowledgment about these words. Theresults show that efforts of Indian media for cultivating their culture in Pakistan issomehow getting successful and in that purpose the greed of cable operators andnegligence of PEMRA is at the peak. Students have taken the phenomena of usingHindi language into their daily routine as normal one without realizing that theutilization of the Hindi language is adversely impacting their native language (Urdu)and again taking them back towards the period/era of colonization.